Systems biology studies of adult paragonimus lung flukes facilitate the identification of immunodominant parasite antigens. - Samantha N McNulty; Peter U Fischer; R Reid Townsend; Kurt C Curtis; Gary J Weil; Makedonka Mitreva (Public Library of Science (PLoS), 2014)
Paragonimiasis is a food-borne trematode infection acquired by eating raw or undercooked crustaceans. It is a major public health problem in the far East, but it also occurs in South Asia, Africa, and in the Americas. Paragonimus worms cause chronic lung disease with cough, fever and hemoptysis that can be confused with tuberculosis or other non-parasitic diseases. Treatment is straightforward, but diagnosis is often delayed due to a lack of reliable parasitological or serodiagnostic tests. Hence, the purpose of this study was to use a systems biology approach to identify key parasite proteins that may be useful for development of improved diagnostic tests.The transcriptome of adult Paragonimus kellicotti was sequenced with Illumina technology. Raw reads were pre-processed and assembled into 78,674 unique transcripts derived from 54,622 genetic loci, and 77,123 unique protein translations were predicted. A total of 2,555 predicted proteins (from 1,863 genetic loci) were verified by mass spectrometric analysis of total worm homogenate, including 63 proteins lacking homology to previously characterized sequences. Parasite proteins encoded by 321 transcripts (227 genetic loci) were reactive with antibodies from infected patients, as demonstrated by immunoaffinity purification and high-resolution liquid chromatography-mass spectrometry. Serodiagnostic candidates were prioritized based on several criteria, especially low conservation with proteins in other trematodes. Cysteine proteases, MFP6 proteins and myoglobins were abundant among the immunoreactive proteins, and these warrant further study as diagnostic candidates.The transcriptome, proteome and immunolome of adult P. kellicotti represent a major advance in the study of Paragonimus species. These data provide a powerful foundation for translational research to develop improved diagnostic tests. Similar integrated approaches may be useful for identifying novel targets for drugs and vaccines in the future.